DEVELOPMENT OF APPLIED MECHANICAL ENGINEERING UNDERGRADUATE CURRICULUM BASED ON INDUSTRY NEEDS - Heri Wibowo; Prihatno Kusdiyarto; Muh Imawan B; Ardani Ahsanul Fakhri (Department of Mechanical Engineering Education, 2025)
The curriculum currently used in many universities is still not fully aligned with industry needs, causing a gap between graduate competencies and workplace expectations. Many graduates experience difficulties in finding employment because their skills do not match industry demands. To overcome this problem, the development of an industry-based curriculum is a strategic solution involving various stakeholders such as industry, academics, and alumni. This study used the Research and Development (R&D) method with the Borg & Gall development model, which includes 10 stages. The results show that the new curriculum for the Mechanical Engineering Applied Bachelor Program emphasizes a greater proportion of practice (60%) compared to theory (40%). This new curriculum is designed to be more relevant to industry needs, integrating the latest technology. Trials of the new curriculum show a 12% increase in students' practical competencies, while the industry partner satisfaction rate reaches 88%, indicating the effectiveness of the new curriculum product.